Treatment of valvular heart disease in young patients—"early evidence" versus "latest fashion". Issue 8 (9th May 2022) - Kirov, Hristo; Caldonazo, Tulio; Doenst, Torsten
Abstract: Is the performance of locally manufactured mechanical valve prostheses relevant for modern cardiac surgery, in which mechanical valve replacement has become a rarity? This question comes to mind reading the article in this issue of the Journal demonstrating equal outcomes of the TTK Chitra tilting disk mechanical heart valve prostheses in comparison to the SJM bi‐leaflet blockbuster. The evidence documenting efficacy of mechanical valve replacement stems from the early ages of cardiac surgery, but often demonstrates superior outcomes in terms of survival and hemodynamics. Yet, the latest fashion in the Western world consists biological choices in combination with new transcatheter techniques (valve in valve options) or the Ozaki or Ross procedures. As long‐term results are often missing and documented advantages for mechanical valves stems from early evidence, the local emphasis of mechanical valve replacement may possibly result in superior individual prognoses compared to following the Western world's latest fashions. Individual patient information and decision making moves into focus.